Time paradox in the Iraqi feminist novel (2003 - 2013) - Wijdan Yakoob Mahmood; Zayneb hadi Hassan (College of Education for Women, 2019)
This paper deals with novels for group of Iraqi Women novelists published in the time period 2003 - 2013, and the functioning of temporal anomalies in the Iraqi Women's narrative. In general, the novel contains structural elements such as: the characters, events and the places, these elements must be collected by an artist creating a complete work of fiction. However the time dominates the other elements through progression and regaining called Time paradox, it has a modern critical importance because of its impact in highlighting of political, social and cultural events that make up the fictional environment which cast a shadow over other techniques. And that it is clear in the course of the narrative.